A blockchain-based secure healthcare scheme with the assistance of unmanned aerial vehicle in Internet of Things. (June 2020) - Islam, Anik; Young Shin, Soo
Abstract: This paper introduces a blockchain-based secure healthcare scheme in which health data (HD) are collected from users via an unmanned aerial vehicle (UAV) and stored on the nearest server. In the proposed scheme, a UAV first establishes a relation with body sensor hives (BSHs) via a token and then shares a shared key with BSHs to enable low-power secure communication. After retrieving the HD, the UAV decrypts the encrypted HD (encrypted by a BSH) using the shared key and exercises a two-phase authentication mechanism. Upon successful validation, the UAV transmits the HD to the nearest server to store it securely in blockchain. A security analysis is discussed to show the feasibility of the proposed secure healthcare scheme. Finally, the performance of the proposed scheme is investigated through simulation and implementation. The security and the performance analysis demonstrate that the proposed scheme supports better assistance to BSHs while maintaining security.